“Moving from understanding to action on food security in Inuit Nunangat”: - Angus Naylor; Tiff-Annie Kenny; Chris Furgal; Dorothy Beale; Duncan Warltier; Marie-Hélène Carignan; Lynn Blackwood; Brian Wade; Gabriela Goodman; Jordyn Stafford; Matthew Little (Canadian Food Studies / La Revue canadienne des études sur l'alimentation, 2023)
This Commentary details key challenges and opportunities relating to the promotion of food security in Inuit Nunangat, discussed as part of the event “Moving from understanding to action on food security in Inuit Nunangat”, convened at the ArcticNet Annual Scientific Meeting on 5th December 2022 in Toronto. The purpose of the event was to explore opportunities for action on food security in northern communities, and to mobilize knowledge on current and future food security programming. A range of stakeholders from across Inuit Nunangat and Canada were involved, including representatives from Inuit Tapiriit Kanatami and Nutrition North Canada, territorial, regional, and community food security co-ordinators and government delegates, academics, and community members. Points of discussion across the day included the integration of culturally appropriate country foods into food programming; the importance of human and financial resources to program success; interactions between COVID-19, climate change, and food security; challenges relating to the classification of “households” in food security surveys; and the crucial importance of school food programs for reducing food and income stress on families.